Pengaruh Live Streaming, Content Marketing Dan Online Customer Review Terhadap Keputusan Pembelian Pada Tik Tok Shop Di Kota Bengkulu - putra, Andika putra; Puspita, Veny; Safrianti, Sintia (JMB : Jurnal Manajemen dan Bisnis, 2024)
This study aims determine how much influence live streaming, content marketing and customer reviews have on purchasing decisions at TikTok Shop in Bengkulu City. study uses a type quantitative research using primary data obtained from a questionnaire. The population in study are Tiktok Shop users who have made purchases. With certain criteria. The dependent variables in this study are live streaming, content marketing and customer review. The sample in this study was 95 respondents, which were determined using the Hair formula. The results of the partial research are Live streaming has a significant effect on purchasing decisions tiktok shop in Bengkulu city. Content marketing has no significant effect on purchasing decisions at the TikTok shop in Bengkulu city. Online customer review has no significant effect on purchasing decisions Tiktok shop in Bengkulu city. while simultaneously stating that Live streaming, content marketing and online customer revew have a simultaneous effect on purchasing decisions at the Tiktok shop in Bengkulu city.